2022
DOI: 10.1111/joim.13536
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and COVID‐19—Revisited

Abstract: Vitamin D, when activated to 1,25‐dihydroxyvitamin D, is a steroid hormone that induces responses in several hundred genes, including many involved in immune responses to infection. Without supplementation, people living in temperate zones commonly become deficient in the precursor form of vitamin D, 25‐hydroxyvitamin D, during winter, as do people who receive less sunlight exposure or those with darker skin pigmentation. Studies performed pre‐COVID‐19 have shown significant but modest reduction in upper respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 120 publications
1
11
0
1
Order By: Relevance
“…Given the low number of patients with combined immunosuppressive therapy in this study, we did not covariate for this potential confounder in our model. Future studies will be required to investigate if third dose SARS‐CoV‐2 vaccine responses in IBD patients are also affected by other potential confounders such as vitamin D deficiency which has been hypothesised to influence severity of COVID‐19 43,44 …”
Section: Discussionmentioning
confidence: 99%
“…Given the low number of patients with combined immunosuppressive therapy in this study, we did not covariate for this potential confounder in our model. Future studies will be required to investigate if third dose SARS‐CoV‐2 vaccine responses in IBD patients are also affected by other potential confounders such as vitamin D deficiency which has been hypothesised to influence severity of COVID‐19 43,44 …”
Section: Discussionmentioning
confidence: 99%
“…Observational data from past studies suggest that low levels of 25(OH)D may be a risk factor for severe COVID-19. [39] However, confounding or random influences may be responsible for this connection [40,41] This study found that the mean calcium level was substantially lower in COVID-19 patients than in the control group. Yang's [44] result that COVID-19 was independently related to hypocalcemia more so than the control group confirmed these similar findings.…”
Section: Discussionmentioning
confidence: 79%
“…7 Other studies investigated the role of vitamin D supplementation on infection severity and outcome. 8,9 The present study aimed to evaluate the clinical and prognostic significance of baseline vitamin D levels in hospitalized Egyptian covid-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Other studies investigated the role of vitamin D supplementation on infection severity and outcome. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%